HUBUNGAN ANTARA KEPEMIMPINAN KEPALA SEKOLAH DAN KETERLIBATAN GURU DALAM PENGAMBILAN KEPUTUSAN DENGAN SIKAP GURU MELAKSANAKAN TUGAS - Thamrin A Kum (Universitas Muhammadiyah Gorontalo, 2015)
The purpose of this study is to look at the relationship of school leadership and teacher involvement in decisionmaking with the attitude of the teacher. This study used survey method through correlational studies. This study was designed to obtain clear information about the symptoms at the time of the study. The survey is generally done to find clear information empirically and will be used to solve a problem. Partial correlation test results provide information that school leadership a greater contribution to the attitudes of teachers carry out tasks when compared with the attitude of the teacher duty. This difference is shown by the coefficient of determination r2 y1.2> r2 y2.1 or 0.2005> 0.1683. Besides this difference is also supported by the results of testing a simple correlation between the variable and variable Y X1 X2 variable Y. This result indicated by the coefficient of determination and r2 y2 r2 y1 = 0.3940 = 0.3663. The existence of a positive relationship between school leadership with teachers' attitudes duties gives the sense that the higher the score the principal's leadership, the higher the attitudes of teachers perform their duties, and conversely the lower the score the ability of school leadership also lower the attitudes of teachers duties